Foreign Language Anxiety in Student’s Speaking and Writing Skills - Dede Rohadi Fajri; Siti Hikmah (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2018)
This research is focusing on the level of Foreign Language Anxiety that experienced by students. In this research, the researcher was use the Qualitative research as the method in implementing case study. The sources of data were 30 students of the second semester of Banten Jaya University. For collecting data that used in this study include classroom observation, questionnaires and interview. The questionnaire used to obtain specific information data was gathered from the participants by FLCAS of Horwitz et all (1986). From the result of FLCAS questionnaire, there were 10 students who felt very anxious with percentage 33.33%, 8 students felt anxious with the percentage 26.67%, 8 students felt mildly anxious with the percentage 26.67%, 4 students felt relaxed with the percentage 13.33% and there was no student who felt very relaxed. Then, the result of WAT questionnaire were 7 students felt very anxious with percentage 23.33%, 8 students felt anxious with the percentage 26.67%, 9 students felt mildly anxious with the percentage 30%, 6 students felt relaxed with the percentage 20% and there was no student who felt very relaxed. Based on the findings of the present study, several conclusions can be made: First, students’ anxiety in speaking showed that the students never felt quite sure of themselves when they were speaking in foreign language class. Second, students’ anxiety in writing above showed that most of students avoided writing in English.